USING CONTEXT CLUES OF NARRATIVE STRUCTURE TO IMPROVE THE STUDENTS VOCABULARY MASTERY : SMPN 1 TOMBOLOPAO - Umar, A. Surya Kharisma; Saiful; Firman (English Language Teaching Methodology, 2023)
This study aimed at finding out the influence of  Using Context Clues of Narrative Structure to the Students Vocabulary Mastery of class VII A SMPN 1 Tombolopao. The method of this research was Pre-Experimental research. Data of the research were collected through Context Clue test (Pre-Test and Post-Test). The sample of this research was the VII A Class students of SMPN 1 Tombolopao. The sample was taken by using purposive sampling technique. Based on the results researcher found that context clue gave positive experience and effect in mastering the vocabulary. Result of research was found by the writer in context clue test from students. commonly described that context clue gave positive experience and effect in mastering the vocabulary. Students were able to put the correct word and get new knowledge in using vocabulary. The English teacher also gave supportive explanation about how this strategy implemented in her class, even there was still gap in teaching method when this strategy implemented in the classroom, but at least it gave them advantages in vocabulary learning. In observation the writer found commonly showed good category when context clue strategy. It gave improvement in teaching and learning activity in English class. Student seen to be attractive, gave participation and asking more often in the classroom as same as their vocabulary understanding.